The Effect of Environmental Management Accounting and Control System Integration on Sustainability Orientation through Sectoral Green Economy Mediation - Pramono, Agus Joko; Suwarno, Suwarno; Amyar, Firdaus; Friska, Renny (International Journal of Energy Economics and Policy, 2023)
The orientation of sustainability within the scope of the company refers to the company’s efforts to create long-term value by taking into account the social, environmental and economic impacts of the company’s business activities. To achieve the goals of organizational development, companies must carry out effective environmental management. Company activities that are inseparable from natural resources must pay attention to the condition of the surrounding environment so as not to cause damage to the environment. The purpose of this study is to analyze how far the influence of environmental management accounting factors and the integration of control systems on the company’s sustainability orientation. Then in this study will also analyze the effect of sectoral green economy as a mediating factor. The use of green economy sectoral factors aims to create an economy that also focuses on environmental protection. The research method used is a quantitative research method. The number of samples used in this study were 512 respondents. Respondents who were sampled were managers and employees of state-owned, mining & plantation companies in Indonesia. The sampling technique used was purposive sampling technique. Then the data were analyzed using SmartPLS software. From the results of the research above, it can be concluded that the environmental management accounting and control system integration variables have a significant effect on sectoral green economy and sustainability orientation. Then the sectoral green economy is also capable of being a good mediating factor in bridging the influence of environmental management accounting and control system integration on sustainability orientation.